2019
DOI: 10.1128/aac.00944-19
|View full text |Cite
|
Sign up to set email alerts
|

RexAB Is Essential for the Mutagenic Repair of Staphylococcus aureus DNA Damage Caused by Co-trimoxazole

Abstract: Co-trimoxazole (SXT) is a combination therapeutic that consists of sulfamethoxazole and trimethoprim that is increasingly used to treat skin and soft tissue infections caused by methicillin-resistant Staphylococcus aureus (MRSA). However, the use of SXT is limited to the treatment of low-burden, superficial S. aureus infections and its therapeutic value is compromised by the frequent emergence of resistance.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 61 publications
(103 reference statements)
8
46
0
Order By: Relevance
“…Therefore, we tested whether ROS produced by the respiratory burst triggers the SOS response and whether this was dependent upon RexAB. To do this, we used a P recA-gfp reporter construct and validated it by showing dose-dependent activity with mitomycin C, a well-established trigger of the SOS response ( 38 ) ( Fig. S6 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we tested whether ROS produced by the respiratory burst triggers the SOS response and whether this was dependent upon RexAB. To do this, we used a P recA-gfp reporter construct and validated it by showing dose-dependent activity with mitomycin C, a well-established trigger of the SOS response ( 38 ) ( Fig. S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to providing protection from oxidative damage caused by neutrophils, we have previously shown that RexAB provides S. aureus with tolerance to the combination antibiotic co-trimoxazole ( 38 ). That work showed that DNA damage was partly due to endogenous oxidative stress that occurred during exposure to the combination antibiotic, in addition to direct damage to DNA caused by thymidine limitation ( 38 ). The data presented here show that the loss of RexAB also sensitizes S. aureus to ciprofloxacin, even though the JE2 strain is resistant.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we tested whether the neutrophil oxidative burst triggers the SOS response and whether this was dependent upon RexAB. To do this we used a P recA-gfp reporter construct and validated it by showing dose-dependent activity with mitomycin C, a well-established trigger of the SOS response 38 (Supplementary Fig. S6).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to providing protection from oxidative damage caused by neutrophils, we have previously shown that RexAB provides tolerance to the combination antibiotic co-trimoxazole 38 . That work showed that DNA damage was partly due to endogenous oxidative stress that occurred during exposure to the combination antibiotic, in addition to direct damage to DNA caused by thymidine limitation 38 . The data presented here show that loss of RexAB also sensitises S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation